Patient Safety Behavior in Physicians: How is it Predicted? - Maryam Yaghoubi; Marzieh Javadi; Saied Karimi; Elham Ehsani (Baqiyatallah University of Medical Sciences, 2016)
Background: Patient safety is a serious global public health issue. Estimates show that every day many patients are harmed while receiving hospital care. Health care staff plays a key role in providing quality and safe patient care, especially physicians who are main members of the medical team and a critical element in patient safety efforts. Objective: The current study used a Theory of Planned Behavior (TPB) framework to investigate predictors of patient safety intentions and behavior of physicians. Methods: This descriptive analytical study was conducted in 8 hospitals with 52 physicians participating. A researcher-designed questionnaire was prepared to investigate patient safety behaviors and behavior constructs of physicians based on the guidelines of constructing a TPB Questionnaire: Conceptual and Methodological Considerations. The content validity and reliability of the questionnaire were confirmed. Binary logistic regression analysis was performed using SPSS18. Results: The total mean score of physician safety behavior indicated that 3.8±0.92. 42% of physicians reported their safety behavior at a good level. There was no significant difference between the patient safety function of physicians in public and private hospitals (P=0.8) and working in medical or surgical wards (P=0.4). Among TPB constructs, "normative beliefs" had the greatest influence on physician intention for safety behaviors (wald=3.828, P=0.05). Conclusion: The results showed that "normative beliefs" had the greatest influence on physician intention for safety behaviors; therefore, it seems that patient safety must be the most important concern of all health care staff, specifically managers and executives throughout health care centers.